FOOD WASTE STATUS AND REDUCTION THROUGH THE CIRCULAR ECONOMY - Mahmoud TARHINI; Vlad-Constantin TURCEA; Luiza-Florentina ZAPUCIOIU; Raluca-Andreea ION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food waste and the circular economy are two major topics that the Earth’s population should be concerned about. The circular economy has been discussed on a regular basis as a mechanism of better waste management through recycling, reuse, and recovery. As a result, this paper’s aim is to reveal a comprehensive look at alternate solution implementations over the whole life cycle of any process, as well as the relationship between processes, environment, and economy. The research question is whether the circular economy is related to food waste, starting from the assumption that food waste can be prevented by applying the principles of circular economy. The findings show that the EU 28 contributes significantly to the global 1.3 billion tonnes of wasted food each year, while the cost of covering the 180 kg/capita of food wasted each year in the EU 28 raises up to 25% of the food products acquired, evidencing a massive monetization and a possible material overturn if this issue of reducing food waste is not properly managed. The relevance of the results consists in the fact that circular economy inspires new patterns and behaviors to consumers, assisting them in achieving greater sustainability. As a result, disposed food is no longer considered as a waste or energy recovery problem, but rather as an opportunity to enhance the overall system.